ANALISIS HIERARKI PUSAT PELAYAN DI KOTA KUPANG - Poppy Haryani; Martina Ayu Sejati; Tugma Jaya Manalu; Febriyanti Angelia Ginting (Jurnal Geografi, 2025)
With Kupang City's subdistricts serving as the analysis unit, this study seeks to determine the hierarchy of service centers. The hierarchy level of service centers is ascertained by the use of centrality indices and scalogram techniques. The results are presented in a hierarchy table based on the presence and completeness of service facilities in each area. In Kupang City, Hierarchy I includes the Oebobo and Maulafa subdistricts, which have more complete facilities and infrastructure and function as primary service centers with significant influence on surrounding areas. Hierarchy II consists of the Alak and Kelapa Lima subdistricts, which, although having more facilities, are not as comprehensive as Oebobo and Maulafa, with lower service quality. Meanwhile, the Kota Raja and Kota Lama subdistricts are in Hierarchy III, with more limited facilities and functioning as local service centers with lower accessibility. The results of this study are expected to provide insights for the local government in planning related to service centers.